Harnessing the Wind: The Impact of Wind Farm Development on Municipal Finances - Claudia Serra-Sala (CESifo GmbH, 2024)
Wind farm development, despite offering global benefits, often encounters local opposition fostered by local negative externalities and uncertain benefits. This study investigates the financial impact of wind farm development on host municipalities using Spanish municipality-level budget data from 1994 to 2022. Results from two-way fixed effect difference-in-difference and event study models show an average 45 percent increase in municipal revenue per capita, funding real investments and current expenditures. This revenue increase, driven by a tax base expansion, is complemented by a rise in capital income and local tax responses in the form of higher tax rates associated with this infrastructure.
Keywords: H20; R10; Q40; 330; energy transition; local public finance; wind power